Pengelolaan Kelas Guru Bahasa Inggris Bersertifikasi PPG di Perguruan Tinggi Negeri - Luthfiani Luthfiani; Hendri Budi Utama; Sari Febrianti (Journal of Educational Administration and Leadership, 2023)
This study aimed to evaluate the effect of the teacher certification program policy (PPG) on English teachers toward their classroom management for English teachers in one public university in Palembang. Gender, age, teaching experience, and school level have been assumed to have a contribution to the participants in managing their classes. The study was designed as a quantitative method with a survey approach by distributing the questionnaire that consists of demographic background information and Attitudes and Beliefs in Classroom Control Inventory (ABCC) by Martin, Yin, and Baldwin (1998) as the data. Logistic regression and T-Test using SPSS 24 had done to analyze the data. The results showed that most participants chose instructional management as the best method in classroom management. Then teaching experience had considered having a high contribution to English certified teacher of PPG to manage the class as defined by Sokal, Smith, and Mowat (2003). This study discovered school level also contributed to participants in classroom management. Though the results showed that all the factors have contributed, the researcher did not find a significant difference between English teachers of PPG in classroom management classified by gender, age, teaching experience, and school level in the T-Test.